Health needs of sex workers. Issue 10 (October 2013) - McGlennan, Catherine; D'Arcy, Rhiannon
The aim of this article is to identify how health care professionals can provide the best care to the population involved in sex work. It aims to take a broad view of the health problems that affect this group of patients, how they differ to the greater population and what strategies need to be taken to make sure that they are effectively reached by health services.